Stability Analysis of the Fluorescent Tracer 1-Methylnaphthalene for IC Engine Applications by Supercontinuum Laser Absorption Spectroscopy - Fendt, Peter; Retzer, Ulrich; Ulrich, Hannah; Will, Stefan; Zigan, Lars (Sensors, 2020)
1-methylnaphthalene (1-MN) is a widely used laser-induced fluorescence (LIF) tracer for planar imaging of mixture formation and temperature distributions in internal combustion (IC) engines. As the LIF measurement results can be biased by partial tracer oxidation, the conversion of 1-MN and the base fuel isooctane is analyzed in a calibration cell. First, measurements using supercontinuum laser absorption spectroscopy (SCLAS) are presented in order to quantify the conversion by detection of the produced H2O mole fraction. A single mode fiber (SMF) coupled setup is presented, with the fiber core acting as entrance slit of a Czerny-Turner spectrometer. Dependencies on residence time and global air-fuel ratio are presented at pressures up to 1.5 MPa and temperatures up to 900 K, at which distinct tracer and fuel consumption is observed. Signal loss due to intense beam steering was partially compensated using a self-stabilizing double-pass setup with a retroreflector.
CRIS-Team Scopus Importer:2020-06-02
Keywords: 1-methylnaphthalene; absorption spectroscopy; combustion diagnostics; fiber optic sensors; laser-induced fluorescence tracer; LIF